Harhauttavat suunnittelumallit ultrapikamuodin verkkokaupoissa - Grönberg, Elsalotta (2025)
In this thesis deceptive patterns in ultra-fast fashion e-commerce are examined. Deceptive patterns are user interface choices designed to intentionally mislead users in a harmful way. These patterns are common in e-commerce, but their use of these patterns in ultra-fast fashion e-commerce has not been extensively studied. This study analyzes the use of deceptive patterns in Shein and Temu using qualitative content analysis and examines users’ experience of these patterns through a survey. Results show that Shein and Temu use deceptive patterns on their e-commerce platforms, especially interface interference and social engineering. Overall, both online stores employed many of the same design patterns, but there were also differences. For example, Shein relies heavily on gamification, whereas Temu makes use of creating barriers to user actions as well as bad defaults. Users’ experiences of these patterns are conflicting. While they generally felt that such patterns affect users in general, it was difficult for them to assess how the patterns influenced their own behavior. Furthermore, users’ ability to identify these patterns varied significantly. Given the broader ethical and sustainability concerns associated with ultra-fast fashion, it is important to raise users’ awareness of these patterns and to encourage e-commerce platforms to adopt more responsible user interface design practices.